ANALYSIS OF CLOUD COMPUTING SERVER NEEDS IN SUPPORTING COMPUTATIONAL PHYSICS LECTURES - Gunawan, Bodi; Cahyani, Diana E (Kumparan Fisika, 2025)
Study of cloud computing needs in supporting Computational Physics Lectures at Bengkulu University has been conducted. The subjects of this study were students who studied computational physics and algorithms. This research aims to examine the urgency of cloud computing implementation in supporting the learning process. In this research, questionnaires were used to collect the data, which included qualitative data types. Descriptive statistics were used in describing the responses and in identifying key trends in the students' perceptions concerning the effectiveness and the necessity of cloud computing tool usage in student coursework. The result of this research showed that 30% of the students did not possess qualified devices to run numerical programming. On the other hand, most of the students have Android devices, and this means that there is a great potential for cloud computing solutions to be used in pursuit of making them better learners. The second important thing that this study has established is that most of the students showed interest in the use of cloud-based applications, which means there is a need for the resources that can be used in bridging the gap to access technologies. That suggests that there is a strong preference on the part of the students for cloud-based resources to help in collaboration and accessibility of coursework.